1979
DOI: 10.1159/000466902
|View full text |Cite
|
Sign up to set email alerts
|

Human IgE Response to the Administration of Blood Components

Abstract: 43 adults from a renal dialysis unit staff have received regularly spaced γ-globulin administrations for hepatitis B prophylaxis. Several blood samples were collected over a prolonged period of time (160 days). Following γ-globulin administration, anti-immunoglobulin antibodies of the IgE class were detected in 80% of this population, a fortnight after the first injection using serum absorptions on polymerized γ-globulins or a specific inverse RAST method. The reactivity pattern of these IgE anti-immunoglobuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1983
1983
1994
1994

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…The authors suggested that antigenic stimulation from the transfusion of platelet and white cells produced hyperactivity of the IgE response. Our study confirms the results obtained by Cartroon et al [4] and Ropars et al [16], even if our thalassemic patients differ in age, type of transfusions and immunologic pattern.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The authors suggested that antigenic stimulation from the transfusion of platelet and white cells produced hyperactivity of the IgE response. Our study confirms the results obtained by Cartroon et al [4] and Ropars et al [16], even if our thalassemic patients differ in age, type of transfusions and immunologic pattern.…”
Section: Discussionsupporting
confidence: 93%
“…Ropars et al [16] studied the IgE response in 94 adult cardiac surgery patients who received massive blood transfusions during bypass procedure. IgE increased over the 2 weeks following surgery and then returned to pretransfusion levels within 2 months.…”
Section: Discussionmentioning
confidence: 99%
“…In the latter case it is noteworthy that total levels of IgG3 may remain normal in spite of infection (18). A similar argument appears to be valid for responses both against autologous protein antigens (such as blood group antigens (A, D and P), which induce IgGl and IgG3 (9) but not IgE (16) and immunglobulins which induce IgGl, IgG4 and IgE (2,8,14,17)) and heterologous antigens (such as tetanus toxoid (IgGl, IgG4 and IgE) (21)). Although these two patterns appear rather consistent, exceptions may exist and trace amounts of the non-preferred subclasses (such as IgG2 and IgG3 or IgG4) may be found in the sera of hyperimmunized individuals.…”
Section: Discussionmentioning
confidence: 72%
“…These observations were supported by the studies of Ropars et al (412) who concluded that only the class-specific anti-IgA antibodies were of importance and that the majority of reactions were due to anti-complementary effects of the gammaglobulin preparations. Elevated titers of IgE anti-IgA were also detected in patients given multiple injections of gammaglobulin, but as with the IgG anti-IgA antibodies, they were of limited specificity and not associated with adverse reactions (413). Only those with antibodies of broad specificity demonstrated an association with intolerance reactions.…”
Section: Anaphylactic Reactionsmentioning
confidence: 89%